Targeting Kinases in Fasciola hepatica: Anthelminthic Effects and Tissue Distribution of Selected Kinase Inhibitors - Morawietz, Carolin M.; Houhou, Hicham; Puckelwaldt, Oliver; Hehr, Laura; Dreisbach, Domenic; Mokosch, Annika; Roeb, Elke; Roderfeld, Martin; Spengler, Bernhard; Haeberlein, Simone (Frontiers in Veterinary Science, 2020)
Protein kinases have been discussed as promising druggable targets in various parasitic helminths. New drugs are also needed for control of fascioliasis, a food-borne trematode infection and worldwide spread zoonosis, caused by the liver fluke Fasciola hepatica and related species. In this study, we intended to move protein kinases more into the spotlight of Fasciola drug research and characterized the fasciolicidal activity of two small-molecule inhibitors from human cancer research: the Abelson tyrosine kinase (ABL-TK) inhibitor imatinib and the polo-like 1 (PLK1) inhibitor BI2536. BI2536 reduced viability of 4-week old immature flukes in vitro, while adult worms showed a blockade of egg production. Together with a significantly higher transcriptional expression of PLK1 in adult compared to immature worms, this argues for a role of PLK1 in fluke reproduction. Both fluke stages expressed ABL1-TK transcripts at similar high levels and were affected by imatinib. To study the uptake kinetic and tissue distribution of imatinib in F. hepatica, we applied matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) for the first time in this parasite. Drug imaging revealed the accumulation of imatinib in different fluke tissues from 20 min to 12 h of exposure. Furthermore, we show that imatinib is metabolized to N-desmethyl imatinib by F. hepatica, a bioactive metabolite also found in humans. Besides the vitellarium, gastrodermal tissue showed strong signal intensities. In situ hybridization demonstrated the gastrodermal presence of abl1 transcripts. Finally, we assessed transcriptional changes of physiologically important genes in imatinib-treated flukes. Moderately increased transcript levels of a gene encoding a multidrug resistance protein were detected, which may reflect an attempt to defend against imatinib. Increased expression levels of the cell cycle-dependently expressed histone h2b and of two genes encoding superoxide dismutases (SOD) were also observed. In summary, our pilot study demonstrated cross-stage activity of imatinib but not BI2536 against immature and adult F. hepatica in vitro; a fast incorporation of imatinib within minutes, probably via the oral route; and imatinib-induced expression changes of physiologically relevant genes. We conclude that kinases are worth analyzing in more detail to evaluate the potential as therapeutic targets in F. hepatica.